Molecular epidemiological analysis of mitochondrial DNA12SrRNA A1555G, GJB2, and SLC26A4 mutations in sporadic outpatients with nonsyndromic sensorineural hearing loss in China - JI, YU-BIN (2010)
CONCLUSION: GJB2 mutation was frequent in sporadic outpatients and its mutation frequency was significant higher in the prelingual group than in the postlingual group, whereas the mutation of mtDNA A1555G and SLC26A4 was very rare in Chinese sporadic outpatients with nonsyndromic sensorineural hearing loss (NSHL). Standard and comprehensive inclusion and grouping criteria are necessary for epidemiological studies of deafness-related gene mutations. OBJECTIVES: This study aimed to examine the mutations of the three common deafness genes GJB2, SLC26A4, and mtDNA A1555G in Chinese sporadic outpatients withNSHLandtodiscussthefactorsthatinfluencethedetection accuracyofmutationfrequencies. METHODS: A total of 473 sporadic NSHL patients without any type of inner ear malformation, including both prelingual and postlingual groups were enrolled in this study. Three genes of mtDNA A1555G, GJB2, and SLC26A4 were screened for mutation in our study cohort. A chi-square test was performed to compare mutation frequencies between prelingual and postlingual groups. RESULTS: The mutation frequencies of MtDNA A1555G, GJB2, and SLC26A4 were 1.63%, 13.63%, and 0%, respectively, in our study cohort. The mutational hot spot of GJB2 was c.235delC, whose allele frequency was 12.68% in sporadic outpatients. Mutation frequency of GJB2 in the prelingual group was significantly higher than in the postlingual group (p < 0.05).